Tantangan dan Peluang Bisnis di Masa Pandemi Covid-19: Menarik Minat Beli Pelanggan melalui Aplikasi E-commerce, Endorsement Selebgram dan Instagram Ads. - Bambang Setia Wibowo (MANAJEMEN DEWANTARA, 2022)
This study aims to determine the business challenges and opportunities during the covid-19 pandemic: attracting customer purchase interest through e-commerce, endorsement celebrities and instagram ads. Some online shops in the marketplace use endorsement celebrities and Instagram ads to attract consumer attention. When celebgrams deliver product advertisements, consumers will follow them because of their reputation, popularity and credibility. This research used survey design with purposive sampling. This research was conducted on 176 students in Yogyakarta who had already done online shopping in the marketplace during the Covid-19 pandemic. Data analysis was performed using Structural Equation Model (SEM) using Analysis Moment Structure (AMOS). This research proves that there is a positive influence on the use of e-commerce, endorsement celebrities and instagram ads on customer buying interest. There are several findings in this study. First, e-commerce has positive influence to the customer buying interest. Second, endorsement celebrities has positive effect to customer buying interest. Third, instagram ads has positive effect to customer buying interest. Keyword: Customer Purchase Interest, E-commerce, Celebrities endorsement, Instagram Ads, Covid-19 Pandemic